Heart surgery for immigrants in Italy: burden of cardiovascular disease, adherence to treatment and outcomes. Issue 2 (February 2016) - Grimaldi, Antonio; Vermi, Anna Chiara; Cammalleri, Valeria; Castiglioni, Alessandro; Pappalardo, Federico; Taramasso, Maurizio; Baratto, Francesca; Alfieri, Ottavio
Abstract : Aim: Italy is a country with high rates of immigration and the knowledge of immigrant health is very fragmentary. We provide a current picture of cardiovascular disease causes and clinical outcomes following heart surgery. Methods: A clinical and echocardiographic survey was conducted on 154 consecutive immigrants referred for heart surgery to San Raffaele Hospital in Milan between 2003 and 2011. Results: Major causes of heart disease were rheumatic heart disease (RHD) ( n = 64, 41%), nonrheumatic valvulopathies ( n = 41, 27%), ischemic heart disease (IHD) ( n = 25, 16%), congenital heart disease ( n = 13, 9%) and miscellaneous ( n = 11, 7%). Median age was 49 years [interquartile range (IQR) 7–81]; 55% of patients were male. Among valvulopathies, rheumatic mitral disease was predominant ( n = 56, 53%) as both single and multivalvular disease ( n = 46, 73%); myxomatous prolapse emerged as the second main pattern of mitral disease ( n = 30, 33%). Among patients with IHD, 72% had a high cardiovascular risk. Surgery was scheduled in 138 patients (90%). Clinical follow-up was available in 96 patients (62%) [median time 62 months (IQR 15–123)], among whom 92 (96%) were alive, four patients (4%) had died and 58 (38%) were lost. Conclusion: Cardiovascular diseases represent a major health topic among immigrants in developed countries. RHD still is the predominant cause of hospitalization for heart surgery, nonrheumatic valvulopathies and IHD emerging as second and third causes, respectively. Data underline the need of reinforcement of prevention and care strategies in the matter of immigrant health and warrant the urgent attention of the international public health and research communities.